2013
DOI: 10.2753/mer1052-8008230113
|View full text |Cite
|
Sign up to set email alerts
|

Building "Brand Me": Creating a Personal Brand Statement

Abstract: Building "Brand Me": Creating a Personal Brand stateMent angela d'auria stanton and Wilbur W. stantonEngaging students in a principles of marketing course can prove challenging but also provides instructors with an opportunity to link course concepts using a real-world orientation. This paper describes the use of a personal brand statement assignment as a way to integrate the key marketing concepts of branding and brand positioning into a broader understanding of marketing. The assignment requires the students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The issue of the curricula for personal branding and the practical challenge of preparing people to be effective personal branders were raised as early as 2005 in academic sources (Shepherd, 2005 ). Out of the 100 reviewed articles, 11 deal with teaching personal branding, suggesting various curricula (Edmiston, 2014 ; Johnson, 2017 ) and estimating effectiveness of different assignments in teaching personal branding skills (McCorkle and McCorkle, 2012 ; Wetsch, 2012 ; Stanton and Stanton, 2013 ; Jones and Leverenz, 2017 ). This review demonstrated that there is limited understanding and concurrence on the concepts and processes; therefore teaching unproven ideas raises ethical issues in itself.…”
Section: Resultsmentioning
confidence: 99%
“…The issue of the curricula for personal branding and the practical challenge of preparing people to be effective personal branders were raised as early as 2005 in academic sources (Shepherd, 2005 ). Out of the 100 reviewed articles, 11 deal with teaching personal branding, suggesting various curricula (Edmiston, 2014 ; Johnson, 2017 ) and estimating effectiveness of different assignments in teaching personal branding skills (McCorkle and McCorkle, 2012 ; Wetsch, 2012 ; Stanton and Stanton, 2013 ; Jones and Leverenz, 2017 ). This review demonstrated that there is limited understanding and concurrence on the concepts and processes; therefore teaching unproven ideas raises ethical issues in itself.…”
Section: Resultsmentioning
confidence: 99%
“…Although many disciplines, such as educational psychology (Dreyer, 2015) and social work (Sage & Sele, 2015), have utilized reflective journaling to enhance learning outcomes and student participation, this technique is less practiced in marketing courses. In addition to the learning benefits of reflective journaling, Stanton and Stanton (2017) find that students engage more with the content and perform better on objective measures (e.g., exam grades). Muncy (2014) utilizes online blogs as a journaling mechanism and shows that this activity results in immersive reflective learning.…”
Section: Reflective Learningmentioning
confidence: 99%
“…Muncy (2014) utilizes online blogs as a journaling mechanism and shows that this activity results in immersive reflective learning. Both Muncy (2014) and Stanton and Stanton (2017) employ online submissions as the mechanism for writing, submitting, and evaluating journal entries.…”
Section: Reflective Learningmentioning
confidence: 99%
“…Reputation management is also discussed in the literature as a way to build a long-lasting personal brand. Since reputation presents someone's success story, both companies and customers draw much more attention and make their key decisions based on the results of tracking one's online presence expecting it to be strong and positive (Labreque et al, 2011;Stanton & Stanton, 2013;Ward & Yates, 2013). One more aspect of (teacher) personal branding that is revealed in the literature is ethics in public relations practice.…”
Section: Literature Reviewmentioning
confidence: 99%